LIVER BIOCHEMISTRY PROFILE IN WHITE-TAILED DEER (ODOCOILEUS VIRGINIANUS) REARED IN CAPTIVITY - Alhuay A., David (2011)
This study was carried out with 23 adult white-tailed deer (Odocoileus virginianus)of both sexes, kept in captivity in the province of Lima to establish reference liverbiochemistry profilevalues (Total and direct bilirubin, total protein, albumin, alanineamino transferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (AF),and gamma glutamyl transferase (GGT). The animals (7 males and 16 females) were from three local zoos and were anesthesyzed with ketamine hydrochloride or with acombination of ketamine hydrochloride and xylazine hydrochloride. Blood samples (7ml) were collected from the saphenous vein in sterile tubes and serum was analyzedusing commercial kits. The values (mean ± SD) were Total Bilirubin: 0.6 ± 0.3 mg/dl;Direct Bilirubin: 0.08 ± 0.06 mg/dl; Total Protein: 6.6 ± 0.7 g/dl; Albumin: 3.6 ± 0.5 g/dl;ALT: 26.0 ± 9.7 UI/l; AST: 87.6 ± 22.9 UI/l; AF: 73.9 ± 33.8 UI/l, and GGT: 42.5 ± 12.6 UI/l.There were no statistical differences due to sex except for total bilirubin and albumin(p<0.05)